2012
DOI: 10.1103/physrevb.86.144504
|View full text |Cite
|
Sign up to set email alerts
|

Geometry-induced reduction of the critical current in superconducting nanowires

Abstract: Reduction of the critical current in narrow superconducting NbN lines with sharp and rounded bends with respect to the critical current in straight lines was studied at different temperatures. We compare our experimental results with the reduction expected in the framework of the London model and the Ginsburg-Landau model. We have experimentally found that the reduction is significantly less than either model predicts. We also show that in our NbN lines the bends mostly contribute to the reduction of the criti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
49
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 24 publications
5
49
0
Order By: Relevance
“…More recently, Clem and Berggren 9 have theoretically demonstrated that sudden increases in the cross section of a transport bridge, as those caused by voltage leads, also produce current crowding effects and the consequent detriment of the critical current, similarly to right-angle bends. These predictions have been independently confirmed experimentally by Hortensius et al 10 and by Henrich et al 11 in submicron scale samples of NbTiN and NbN, respectively, and found to be also relevant in larger samples. 12 The effect of a magnetic field applied perpendicularly to the plane containing the superconducting wire with a sharp turn has been discussed in Refs.…”
supporting
confidence: 73%
“…More recently, Clem and Berggren 9 have theoretically demonstrated that sudden increases in the cross section of a transport bridge, as those caused by voltage leads, also produce current crowding effects and the consequent detriment of the critical current, similarly to right-angle bends. These predictions have been independently confirmed experimentally by Hortensius et al 10 and by Henrich et al 11 in submicron scale samples of NbTiN and NbN, respectively, and found to be also relevant in larger samples. 12 The effect of a magnetic field applied perpendicularly to the plane containing the superconducting wire with a sharp turn has been discussed in Refs.…”
supporting
confidence: 73%
“…The strength of the suppression is dependent on the particular geometry of the superconducting structure as well as on the angle and the radius r of the bend and the ratio of the coherence length to the width of the strip ξ GL /w. Several experiments by different groups [29][30][31] have confirmed the predictions of [28]. It has been shown that the current crowding is stronger for wider superconducting strips but becomes weaker with an increase of the radius of the bend.…”
Section: Stationary State Of Snspdmentioning
confidence: 58%
“…It is well known that the presence of current crowding in the bends of a wire can cause reduction of the device critical current by as much as 40% [42], with typical values of 10-20% [43]. We have assumed I b /I c ≈ 0.9 for all devices to produce Figure 4.…”
mentioning
confidence: 99%